The Innovative Learning Institute for Circumpolar Health. An International summer school for nursing students in rural and remote areas - Norbye, Bente; Cheetham, Nina Bøhle (Orkana forlag, 2020)
This chapter focusses on nursing students’ opportunities for participation in an international summer school specifically aimed at the people living in the circumpolar regions. The Northern Nursing Education Network offers a two-week intensive course for students to meet and to develop contextual knowledge of indigenous people living in Arctic regions. These areas are often challenged by vast distances and specific health issues. The summer school is made possible by collaboration across three continents and rotates between the northern universities. The topics about which the students learn are made relevant for nursing practice through peer student meetings, lectures and field trips. This chapter highlights the experiences of the students.